Effectiveness of Topical use of Onion and Ginger for Joint Pain - Cynthia, Fransisca; Priskila, Onny; Ang, Suryawan; Sugiyono, Agus; Ferdinand, Ferdinand (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Onion and ginger have been widely used as painkillers empirically. Its use is always associated with administration by mouth rather than application to the skin. Elderly people often experience joint pain in connection with their aging condition or because of the disease they suffer. Objective: This literature study is to determine the effectiveness of giving onion and ginger as pain relievers in topical administration to joint pain areas. Method: literature study with inclusion criteria, namely: articles including primary literature, articles in English or Indonesian, articles containing onion for topical joint pain, articles containing ginger for topical joint pain, research articles available in full text, and articles in the form of original articles. Result and Discussion: Three journals were found with a total of 101 elderly respondents suffering from joint pain. Given shallot compresses, 10% and 20% ginger cream, and ginger plaster Measurement of the pain scale by means of the visual analog scale and the WOMAC questionnaire The results showed that all groups of shallot compresses, 10% and 20% ginger cream, and ginger plaster reduced the joint pain of elderly respondents compared to the control group. Conclusion: Based on the literature study conducted, it is concluded that the administration of onion and ginger is effective for reducing joint pain in the elderly in all types of topical administration, whether given in the form of compresses, extract creams, or plasters